Interpretação de provas de carga dinâmicas em estacas hélice contínua - Silva, Felipe Correa da [UNESP] (2016)
The dynamic load tests represent a major breakthrough in the level of reliability for foundations, they give support to the engineer in the upcoming decisions throughout the enterprise. This paper studies the interpretation of results from a dynamic test carried out in ten continuous flight auger piles from the JM 600 Office & Mall located at Arujá. Initially they were made load capacity forecasts by the methods of Décourt-Lent and Urban Alonso, based on five SPT tests performed on the ground, for comparison with the curve obtained by the CAPWAP method. From the data provided by the PDA load-settlement curves were extrapolated by the method Van Der Veen (1953) modified by Aoki (1979) in order to meet the load capacity for the application of the method provided by the NBR 6122/2010 and the method used the British standard BS 8004. It can be said, with the comparison between the final results and the forecasts that the dynamic load tests described well the real strength of the piles and the CAPWAP analysis method used by the device ensures a good level of reliability for this tests